Non-fitting theoretical models for the fracture properties of concretes subjected to high temperature. (1st June 2023) - Wan, Yu; Wang, Ruzhuan; Liu, Yumeng; Zhou, Shan; Cai, Hongwei; Gu, Mingyu; Li, Dingyu; Li, Weiguo
Abstract: The fracture properties of concretes, which are often characterized by the tensile fracture strength, compressive fracture strength, fracture energy and characteristic length are closely related to temperature. However, there are still few systematic theoretical models of temperature-dependent fracture properties of concretes. In this work, a series of novel temperature-dependent theoretical models are developed to determine the fracture properties of concretes based on the force-heat equivalence energy density principle and classical concrete fracture theories. The models establish the quantitative relationship between the high-temperature tensile fracture strength, compressive fracture strength and characteristic length, and the basic material parameters including the Young's modulus and melting point. It is worth noting that this work quantitatively characterizes the fracture properties of concretes subjected to high temperatures using the simple material parameters, without the need to carry out any data fitting. The fracture properties of concretes with different aggregate types, different fiber-reinforced concretes, and ordinary Portland cement-based concretes are predicted and systematically analyzed using the proposed models. The model-predicted tensile fracture strength, compressive fracture strength and characteristic length of materials up to 800 °C agree well with the experimental measurements without using any fitting parameters. The coincidence rate at many temperature points could reach up to and above 90%, even approaching about 100%. The fracture properties of concretes and their main mechanisms at various temperatures thus can be depicted by using the developed models. Additionally, this work offers a new and simple testing method to determine the characteristic length of concretes and its change with temperature. Highlights: Temperature-dependent fracture behavior of concrete is quantitatively characterized. The proposed theoretical models have no fitting parameters. The proposed theoretical models are validated by comparing with experimental data. Young's modulus and melting point control fracture behavior at high temperature. A new simple testing method for high temperature characteristic length is revealed.